Study Of Clove Plant Cultivation Techniques (Syzygium aromaticum L.) In Sangihe Islands Regency. - Frit J. Simon; Jelie V. Porong; Tommy B. Ogie (Sam Ratulangi University, 2022)
Cultivation of clove plants is very necessary in the field of agriculture. This research aims to review clove cultivation techniques in Sangihe Islands Regency. The research was conducted in Sangihe Islands Regency, Central Tabukan Village Kuma One Hamlet One, Two and Three. This study uses survey methods. To obtain data from farmers using questionnaires compiled according to clove cultivation techniques. The number of farmers surveyed was forty-eight. Conduct interviews in person to farmers, using questionnaires. The questionnaire data collection is then analyzed percentage values and displayed in table form. Results showed that the cultivation of clove plants (Syzygium aromaticum L.) In kuma Village one hamlet one, two and three Central Tabukan Districts sangihe islands regency declared already in accordance with the recommended clove plant cultivation technique.Keywords: Cultivation, Clove Plants, Middle Tabukan Subdistrict.AbstrakBudidaya tanaman cengkeh sangat diperlukan dalam bidang pertanian. Penelitian ini bertujuan untuk mengkaji teknik budidaya tanaman Cengkeh di Kabupaten Kepulauan Sangihe. Penelitian dilaksanakan di Kabupaten Kepulauan Sangihe Kecamatan Tabukan Tengah Desa Kuma Satu Dusun Satu, Dua Dan Tiga. Penelitian ini menggunakan metode survey. Untuk memperoleh data dari petani menggunakan kuesioner disusun sesuai teknik budidaya cengkeh. Jumlah petani yang disurvey sebanyak empat pulu delapan orang. Melakukan wawancara secara langsung kepada petani, menggunakan kuesioner. Pengumpulan data kuesioner kemudian dianalisis nilai presentase dan ditampilkan dalam bentuk tabel. Hasil menunjukan bahwa budidaya tanaman Cengkeh (Syzygium aromaticum L.) Di Desa kuma satu dusun satu, dua dan tiga Kecamatan Tabukan Tengah Kabupaten Kepulauan Sangihe dinyatakan sudah Sesuai dengan teknik budidaya tanaman cengkeh yang dianjurkan.Kata Kunci : Budidaya, Tanaman cengkeh, Kecamatan Tabukan tengah